KONDISI DARURAT PERSPEKTIF HAKIM DALAM MENGABULKAN DISPENSASI NIKAH ( Studi Kasus di Pengadilan Agama Kabupaten Kediri) - Daimul Hidayah; Moh. Fahimul Ulum (Institut Agama Islam Hasanuddin Pare, 2025)
This research aims to examine the construction of judges’ considerations in assessing urgent reasons in marriage dispensation cases at the Religious Court of Kediri Regency. Marriage dispensation is granted to underage couples who do not meet the legal age requirement, based on certain urgent grounds. The study uses a qualitative-descriptive method with a case study approach. Data were obtained through interviews, documentation, and literature review. The findings reveal that judges consider several aspects, including legal, psychological, socio-cultural factors, and the principle of the best interests of the child. The most common urgent reason is premarital pregnancy. However, the absence of a concrete definition of “urgent reason” in Supreme Court Regulation (PERMA) Number 5 of 2019 leads to subjective interpretations and potential inconsistencies in court decisions. Therefore, clearer guidelines are needed to ensure that marriage dispensation rulings genuinely prioritize child protection